Fundamentals of Engineering Thermodynamics - Rathakrishnan (2006)
Thermodynamics
43969a.jpg;43969b.jpg;43969c.jpg;43969d.jpg;43969e.jpg;43969f.jpg;43969g.jpg;43969h.jpg;43969i.jpg;43969j.jpg;43969k.jpg
22.5
Keywords: Thermodynamics